Discovery and pharmacological characterization of a novel potent inhibitor of diacylglycerol-sensitive TRPC cation channels - Maier, T (Br J Pharmacol, 2015)
BACKGROUND AND PURPOSE: The cation channel transient receptor potential canonical (TRPC) 6 has been associated with several pathologies including focal segmental glomerulosclerosis, pulmonary hypertension and ischaemia reperfusion-induced lung oedema. We set out to discover novel inhibitors of TRPC6 channels and investigate the therapeutic potential of these agents. EXPERIMENTAL APPROACH: A library of potential TRPC channel inhibitors was designed and synthesized. Activity of the compounds was assessed by measuring intracellular Ca(2+) levels. The lead compound SAR7334 was further characterized by whole-cell patch-clamp techniques. The effects of SAR7334 on acute hypoxic pulmonary vasoconstriction (HPV) and systemic BP were investigated. KEY RESULTS: SAR7334 inhibited TRPC6, TRPC3 and TRPC7-mediated Ca(2+) influx into cells with IC(50)s of 9.5, 282 and 226 nM, whereas TRPC4 and TRPC5-mediated Ca(2+) entry was not affected. Patch-clamp experiments confirmed that the compound blocked TRPC6 currents with an IC(50) of 7.9 nM. Furthermore, SAR7334 suppressed TRPC6-dependent acute HPV in isolated perfused lungs from mice. Pharmacokinetic studies of SAR7334 demonstrated that the compound was suitable for chronic oral administration. In an initial short-term study, SAR7334 did not change mean arterial pressure in spontaneously hypertensive rats (SHR). CONCLUSIONS AND IMPLICATIONS: Our results confirm the role of TRPC6 channels in hypoxic pulmonary vasoregulation and indicate that these channels are unlikely to play a major role in BP regulation in SHR. SAR7334 is a novel, highly potent and bioavailable inhibitor of TRPC6 channels that opens new opportunities for the investigation of TRPC channel function in vivo.